2006
DOI: 10.1021/la060439q
|View full text |Cite
|
Sign up to set email alerts
|

Fabrications of Hollow Nanocubes of Cu2O and Cu via Reductive Self-Assembly of CuO Nanocrystals

Abstract: In this work, a template-free synthetic approach for generating single-crystalline hollow nanostructures has been described. Using the small optical band-gap cuprous oxide Cu(2)O as a model case, we demonstrate that, instead of normally known spherical aggregates, primary nanocrystalline particles can first self-aggregate into porous organized solids with a well-defined polyhedral shape according to the oriented attachment mechanism, during which chemical conversion can also be introduced. In contrast to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
304
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(325 citation statements)
references
References 56 publications
20
304
1
Order By: Relevance
“…Although the exact mechanism for the formation of PbS nano-microcrystals is still under investigation, DMF plays an important role. DMF solvent can act as a weak reducing agent [14], therefore, S can be reduced to S 2− in DMF and Pb 2+ then react with S 2− to form PbS nuclei. The initial products are nanocubes, however, {100} faces grow faster than {111} faces with the extension of time, which results in the trunctued nanocubes.…”
Section: Methodsmentioning
confidence: 99%
“…Although the exact mechanism for the formation of PbS nano-microcrystals is still under investigation, DMF plays an important role. DMF solvent can act as a weak reducing agent [14], therefore, S can be reduced to S 2− in DMF and Pb 2+ then react with S 2− to form PbS nuclei. The initial products are nanocubes, however, {100} faces grow faster than {111} faces with the extension of time, which results in the trunctued nanocubes.…”
Section: Methodsmentioning
confidence: 99%
“…Based on an illustrative drawing, it was argued that for solid spheres composed of numerous small particles, the small particles in the inner cores have high surface energies compared to those in the outer surfaces, because they can also be visualized as smaller spheres having a higher curvature. Although fundamental evidence in support of this mechanism is lacking, it has been shown to be applicable in many systems, including TiO 2 , [275][276][277] Cu 2 O, [278,279] ZnS and Co 3 O 4 , [280] Sb 2 S 3 , [281] Ti 1-x Sn x O 2 , [282] Fe 3 O 4 , [283] and ZnO. [284] Interestingly, in the synthesis of Cu 2 O hollow structures, [278,279] TiO 2 hollow spheres, however the product also contains significant fraction of fluorine.…”
Section: à3mentioning
confidence: 99%
“…[269] Cu 2 O hollow nanocubes have been synthesized through reductive self-assembly of CuO nanocrystals followed by inside-out Ostwald ripening. [278] Wang et al have recently demonstrated an extremely simple route that transforms preformed silver solid nanostructures to corresponding hollow ones with unaltered morphologies. [350] The method involves the modification of the solid silver nanoscrystals with dithiol molecules, and subsequent ultrasound-triggered formation of thin layer of sulfide and selective dissolution of the interior and re-deposition on the shell.…”
Section: Template-free Synthesis Of Non-spherical Hollow Structuresmentioning
confidence: 99%
“…A possible explanation for this unique behavior includes an oriented attachment-like mechanism for the assembly of Eu(OH) 3 primary nanoparticles. Previous work [29,30] suggested primary nanoparticles can assemble with a preferential axis, even though these building blocks do not assemble with perfect registry. Ostwald ripening of the surface could grow facets while leaving the rod center with polycrystalline disorder.…”
mentioning
confidence: 98%